Thermosensitive Pluronic® F127-Based in situ gel formulation containing nanoparticles for the sustained delivery of paclitaxel - Sedat Unal; Merve Celik Tekeli; Osman Dogan; Yesim Aktas (Medicine Science, 2023)
Bone metastasis is one of the most encountered complications among cancer patients and majority of cancer types has led to bone metastasis. Paclitaxel (PCX) is an anticancer agent commonly used in cancer treatment. However, its clinical use is restricted owing to poor water solubility. PCL NPs were investigated to cope with solubility problem of PCX. The size, polydispersity index and zeta potential of PCL were 383.8±2.4 nm, 0.253±0.122 and +51.3±6.1 mV, respectively. The PCX encapsulation efficiency was 77.2±2.1%. Subsequently, in situ gellling system was prepared by using different Pluronic F-127 concentration in order to determine the optimum ratio. İn situ gel formulation containing 20% Pluronic F-127 was selected as the optimum formulation and subjected to characterization tests. The viscosity of in situ gelling system with CS/PCX-PCL NPs at room temperature (25 °C±0.1) and at body temperature (37 °C±0.1) were found 137.00 ±3.05 cP and 890.30 ±89.61 cP at 100 rpm, respectively. According to the release results, in situ gel provided prolonged release profile compared to PCL NPs alone. Consequently, in situ gel containing CS/PCX-PCL NP elucidated in detail is a promising approach for locally applicable injectable systems. [Med-Science 2023; 12(1.000): 224-30]